Вы находитесь на странице: 1из 21

.

11 2012



.
.


.
.



.
.


.
.





dx d 2 x
F t, x,
, 2 =0
dt dt



dy d 2 y
,
= 0.
(1)
F x, y ,
dx dx 2

.


F x, y , y 0 , y 00 , . . . , y (n) = 0.
(2)


.
.

Example
F (x, y , z, u) =
x).

2y z
1 (1) (F
u

2y y 0
1=0
y 00

y 00 = 2y y 0 .

xy 0 + y 2
(2).
1 y0
F .

y 00 =

(3)


.
.



.
.


.
.

.
( )
y = y (x) (a, b)
(2)
y (n) x (a, b)


F x, y (x), y 0 (x), y 00 (x), . . . , y (n) (x) = 0.
Example
, y = e2x (3).
. y 0 = 2e2x , y 00 = 4e2x .
2y y 0 = 2e2x (2e2x ) = 4e2x

y 00 = 2y y 0 .
.


.
.

Example

y 00 = f (x)

(4)

y = (x) + c1 + c2 x,

(5)


(x) - , c1 , c2
.
, y 00 = 00 (x) = f (x). , f (x) = 1.
(x) = x 2 /2 (). (5)
(4).


.
.

( )

y = (x, c1 , c2 )
F (x, y , y 0 ) = 0,
1

c1 , c2
(x) = (x, c1 , c2 )

y = (x) (2)
c1 , c2 (x)
(x, c1 , c2 ).

(6)


.
.



.
.


.
.

y (n) = f (x, y , y 0 , . . . , y (n1) )

(7)


y (x0 ) = 0 , y 0 (x0 ) = 1 , . . . , y (n1) (x0 ) = n1 .
,
,
(7)
(8). ,
n C1 , C2 , . . . , Cn .

(8)


.
.


Example
y 00 = 2x(y 0 )2 . y ,
y 0 = z :
z 0 = y 00 ,

z 0 = 2xz 2 .

dz
2 = 2x dx,
z
1
= x 2 + C1 .
z
y0 = z =

1
.
x 2 + C1

, C1 = a2 > 0, y = a1 arctg xa + C2 . C1 = 0
C1 < 0 .
.



.
.


(7) y ,

f (x, y , y 0 , . . . , y (n1) ) = p0 (x)y + p1 (x)y 0 + + pn1 (x)y (n1),
,
a0 (x)y (n) + a1 (x)y (n1) + + an (x)y = f (x).

(9)

, a0 , . . . , an
(a, b), a0 (x) 6= 0.
,
x0 (a, b) .
(9) ,

a0 (x)y (n) + a1 (x)y (n1) + + an (x)y = 0.
.

(10)

(9)
y = y + C1 y1 + C2 y2 + + Cn yn ,
y - , y1 , . . . , yn
(10),
C1 , . . . , Cn .

(11)



.
.

a0 (x)y 00 + a1 (x)y 0 + a2 (x)y = 0

(12)


y = C1 y1 (x) + C2 y2 (x),
y1 (x) y2 (x) .
y = ekx .
,
a0 k 2 ekx + a1 kekx + a2 ekx = 0,
,
a0 k 2 + a1 k + a2 = 0.
.
.

(13)


k1 k2 ,

y = C1 e k 1 x + C2 e k 2 x .
k1,2 = i,
.
eix = cos x + i sin x

y = C1 ex cos x + C2 ex sin x.
, ,
y = C1 ekx + C2 xekx .
.


Example
y 00 + 4y 0 + 3y = 0, y 00 + 4y 0 + 4y = 0
y 00 + 4y 0 + 13y = 0.

k 2 + 4k + 3 = 0. k1 = 3,
k2 = 1,
y = C1 e3x + C2 ex .
k = 2 ,
y = C1 e2x + C2 xe2x .
k 2 + 4k + 13 = 0.
k1,2 = 2 3i.
y = e2x (C1 cos 3x + C2 sin 3x).
.



.
.

a0 (x)y 00 + a1 (x)y 0 + a2 (x)y = f (x)

(14)


y = C1 y1 (x) + C2 y2 (x) + y
y1 (x) y2 (x)
()
, y - .